Kinematic boundary conditions substantially impact in silico ventricular function. (7th October 2018) - Peirlinck, Mathias; Sack, Kevin L.; De Backer, Pieter; Morais, Pedro; Segers, Patrick; Franz, Thomas; De Beule, Matthieu
Abstract: Computational cardiac mechanical models, individualized to the patient, have the potential to elucidate the fundamentals of cardiac (patho‐)physiology, enable non‐invasive quantification of clinically significant metrics (eg, stiffness, active contraction, work), and anticipate the potential efficacy of therapeutic cardiovascular intervention. In a clinical setting, however, the available imaging resolution is often limited, which limits cardiac models to focus on the ventricles, without including the atria, valves, and proximal arteries and veins. In such models, the absence of surrounding structures needs to be accounted for by imposing realistic kinematic boundary conditions, which, for prognostic purposes, are preferably generic and thus non‐image derived. Unfortunately, the literature on cardiac models shows no consistent approach to kinematically constrain the myocardium. The impact of different approaches (eg, fully constrained base, constrained epi‐ring) on the predictive capacity of cardiac mechanical models has not been thoroughly studied. For that reason, this study first gives an overview of current approaches to kinematically constrain (bi) ventricular models. Next, we developed a patient‐specific in silico biventricular model that compares well with literature and in vivo recorded strains. Alternative constraints were introduced to assess the influence of commonly used mechanical boundary conditions on both the predicted global functional behavior of the in‐silico heart (cavity volumes, stroke volume, ejection fraction) and local strain distributions. Meaningful differences in global functioning were found between different kinematic anchoring strategies, which brought forward the importance of selecting appropriate boundary conditions for biventricular models that, in the near future, may inform clinical intervention. However, whilst statistically significant differences were also found in local strain distributions, these differences were minor and mostly confined to the region close to the applied boundary conditions. Abstract : Given the large variation in non‐image derived ventricular boundary conditions found in literature, this study assesses the effect that these mechanical constraints have on in silico ventricular functioning. Commonly used and newly proposed kinematic boundary conditions were applied on a calibrated and validated patient‐specific biventricular model, and both global and local predicted mechanical behavior were compared. Statistically significant and meaningful differences were found between different mechanical anchoring strategies, which brought forward the importance of selecting appropriate boundary conditions.